(untitled) (Research, Society and Development, 2023)
The T-wave in the canine electrocardiogram can be positive, negative, or biphasic in most leads, while his amplitude should not be greater than 25% of the R wave. However, since the 1960’s persists controversy regarding the polarity of the T wave in Chihuahuas when compared to other canine breeds. This study aimed to clarify the polarity and shape of the T-wave in the lead V-10 in a group of healthy Chihuahuas. Retrospective eletrocardiographic study with a sample of 20 private client-owned Chihuahuas. The conclusion was that the polarity of the T-wave is usually negative and the shape is asymmetric, type “slow-fast/down-up”, in all dogs studied.